2016
DOI: 10.1002/suco.201500029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, durability and hygrothermal properties of concrete produced using Portland cement-ceramic powder blends

Abstract: Blended Portland cement‐ceramic powder binder containing up to 60 % fine‐ground waste ceramics from a brick factory is used in concrete mix design as an environmentally friendly alternative to the commonly used Portland cement. The experimental analysis of basic physical characteristics, mechanical and fracture‐mechanical properties, durability properties and hygrothermal characteristics shows that the optimal amount of ceramic powder in the mix is 20 % of the mass of blended cement. The decisive parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…When CBP is used in the absence of RA (series CBP5-RA0, CBP10-RA0, and CBP15-RA0) there are no significant variations with respect to the values obtained for the CC. These results agree with the ones obtained by Kulovaná et al [22], who concluded that the use of up to 20% of CBP does not affect the compressive strength of concretes. The chemical composition of CBP and the grain size distribution of its particles, with a maximum size of 35 µm (Figure 4), made CBP present higher Blaine values than the reference cement, provoking a filler effect that, added to the pozzolanic characteristics, reduces the capillarity, resulting in denser matrixes with similar strengths to the CC [46].…”
Section: Compressive Strengthsupporting
confidence: 93%
See 1 more Smart Citation
“…When CBP is used in the absence of RA (series CBP5-RA0, CBP10-RA0, and CBP15-RA0) there are no significant variations with respect to the values obtained for the CC. These results agree with the ones obtained by Kulovaná et al [22], who concluded that the use of up to 20% of CBP does not affect the compressive strength of concretes. The chemical composition of CBP and the grain size distribution of its particles, with a maximum size of 35 µm (Figure 4), made CBP present higher Blaine values than the reference cement, provoking a filler effect that, added to the pozzolanic characteristics, reduces the capillarity, resulting in denser matrixes with similar strengths to the CC [46].…”
Section: Compressive Strengthsupporting
confidence: 93%
“…Kulovaná et al [22] studied concretes using up to 60% of CBP as a cement replacement for a water/cement ratio of 0.4. Their conclusions show that replacing 20% of the cement does not compromise the mechanical and physical properties of the concretes, and furthermore, the use of this material improves the thermal conductivity by up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Its pozzolanic activity is produced as a consequence of the transformation of crystalline structures of clay silicates in amorphous compounds along the manufacture process of bricks [17], in which clay is exposed to high temperatures, ranging from 600ºC to 1000ºC. Other researches about the use of brick powder in mortars and concretes [10,[18][19][20] have pointed out that a cement replacement up to a 20% of brick powder could be suitable, and it would not affect the physical and mechanical properties of the material. Moreover, it has been noted that the particle size is an important factor in order to insure an adequate behaviour of this addition [21], and it has also been pointed out that the best mechanical strength performance is obtained when the particle size of brick powder is less than 0.06 mm [22].…”
Section: Ofmentioning
confidence: 99%
“…Concrete is the most widely used building material in civil engineering and its durability has always been the focus of attention . Many factors affect the durability of concrete, such as reinforcement corrosion, freeze–thaw cycles, concrete carbonization, and chloride ion erosion, which are directly influenced by moisture transportation .…”
Section: Introductionmentioning
confidence: 99%